Assessing the Management of Facilities and Infrastructure in Madrasah: A Comprehensive Study - Nadia Ayuna; Nuurul Fauziyatil Jannah; R Naila Imtiyazi (Al-Qalam Institue, 2023)
The research focuses on managing facilities and infrastructure in a State Madrasah Aliyah. It can be centered around evaluating the physical condition of facilities, the effectiveness of management practices, the impact of infrastructure on learning, and stakeholder involvement. This research aims to provide a comprehensive overview of the facility conditions, management efficiency, the influence of infrastructure on learning, and the engagement of relevant stakeholders in educational facility management. Identifying a facility and infrastructure management can be seen from the planning, implementation, supporting, and inhibiting factors. This study uses a qualitative approach with a descriptive analysis method. Data collection techniques in this study were done through interviews, observation, and documentation. The data analysis is done through data reduction, display, and conclusion. The results of this study indicate that Management Planning for Facilities and Infrastructure for MAN 2 Bandung City is carried out by involving the community of MAN 2 Bandung City. The madrasah implements a process of five stages: procurement, Inventory, use, maintenance, and disposal. Supporting factors are human resources committees, while inhibiting factors are limited costs, especially in adding areas and buildings.